Quality of Education and Innovation-Driven Development: the New Ukrainian School Reform in the Context of Global Trends - Kremen , Vasyl G.; Hrynevych , Liliia M.; Lugovyi , Volodymyr I.; Talanova , Zhanneta V. (Science and Innovation, 2024)
Introduction. Accelerating human progress is a result of the growing role of innovations. This requires the development of an innovative person as an effective actor of their implementation and support. Primary, and secondary education is very important factor for this. The New Ukrainian School (NUS) reform that has been being implemented since 2016 shall adequately meet current challenges and trends. Problem Statement. To this end, it is very important to identify the key intra-system and contextual factors influencing the quality of school education, first of all in reading, mathematics, and natural sciences, in terms of the development of an innovative person. Purpose. The purpose of this research is to determine the endogenous (internal) and exogenous (external) factors that effectively influence the educational quality, in order to optimize the NUS implementation in the present-day conditions. Materials and Methods. Multifactor system analysis (in particular statistical, correlation, and comparative techniques) of big global databases on human development, international assessment of the quality of primary and basic secondary education, development of world research and university spheres and features of the NUS implementation in Ukraine. Results. The probable global connections between the quality of school education and the factors of internal educational and external contextual impact on the educational quality have been identified. Among the considered nine factors effecting the quality of student education in reading, mathematics, and science, the most influential (resonant) and stable are the endogenous ones, namely, the mean years of schooling, and the share of R&D expenditure in GDP, with the latter having a greater impact. The recommendations for improving the efficiency of the NUS have been given. Conclusions. The effectiveness of school education reform, in particular, NUS, may be raised by taking into account the deterministic effect of endogenous and exogenous factors on the quality of education.